The motivation for playing football among students - E.V. Hotenceva; T.A. Shpichka (Physical Education of Students, 2013)
The aim is to identify factors contributing to increased motivation to playing football in a system of fitness training. Soccer is considered as a form of recreational activity. The study included 30 boys and 30 girls 17-21-year-old. In the process we used the method of sociological research. It is shown that a positive attitude toward physical education formed the majority of students. Found that for most students, classes recreational games are a means of promoting health, well-being, improve the physique. Established internal and external factors that encourage students to sports and recreational activities. Recommendations to improve the motivation of students to playing football.